INVESTIGATION OF LIFE SATISFACTION, MEANING IN LIFE AND LONELINESS LEVELS OF A GROUP OF ELDERLY INDIVIDUALS IN TERMS OF SOME DEMOGRAPHIC VARIABLES - (:unkn) unknown (My University, 2016)
Bu araştırmanın amacı yaşlı bireylerin, bazı demografik değişkenlerle birlikte, yaşam doyumu, yaşamın anlamı ve yalnızlık düzeyleri arasındaki ilişkiyi incelemektir. Bu araştırmada, uygun / elverişli örnekleme yöntemiyle İstanbul ilinin Fatih ve Kağıthane semtlerinde yaşayan 60 yaş ve üzeri 96 katılımcıya (51 erkek, 45 kadın) "Yaşamın Anlamı Ölçeği", "Yaşam Doyum Ölçeği" ve "UCLA Yalnızlık Ölçeği" uygulanmıştır. Araştırmada yaşamın anlamı, yaşam doyumu ve yalnızlık düzeyleri puanları demografik değişkenlere göre farklılaşmamıştır (p>,05). Ancak yaşamın anlamı ve yaşam doyum düzeyleri arasında anlamlı bir ilişki bulunmuştur (r=,266; p<,01). Bu araştırmadaki bulgular, yaşlılık psikolojisi alanında önemli veriler sunmaktadır. Cinsiyet, yaş vb. değişkenlerden öte yaşlı bireyin yaşama nasıl baktığı, onun hayat kalitesini belirleyen bir unsurdur. Yaşlı bireyin kendi varoluş sebebini hatırlatan bir yaşam sürdürdükçe yaşamın her dakikasından tat alabileceğini bizlere göstermektedir

In this regard, the purpose of this study was to analyze the degrees of older individuals' life satisfaction, meaning of life and loneliness within the frame of dynamics of life. In accordance with this aim, "Meaning in Life", "Life Satisfaction Scale" and "UCLA Loneliness Scale" were applied to 96 participants (51 males and 45 females at the ages of 60 and above) living in Fatih and Kağıthane in İstanbul. The participants were selected via the method of convenient sampling. In the study, life-meaning, life-satisfaction and loneliness scores did not show significant differences with regards to demographic variables (p>,05). Yet, it was found that there was a statistically meaningful relationship between the levels of life meaning and life satisfaction (r=,266; p<,01). The findings of this study presents crucial information about psychlogy of older adults. Beyond gender, age and so on the perspectives of older people toward life is an important factor determining the quality of his life. It shows us that as the older adults will get satisfied with every minute of his life as long as they lead a life reminding them of the reason for their existence
Bir Grup Yaşlı Bireyin Yaşam Doyumu, Yaşamın Anlamı ve Yalnızlık Düzeylerinin Bazı Demografik Değişkenler Açısından İncelenmesi
Keywords: Tarih